Microvascular Structural Alterations in Cancer Patients Treated With Antiangiogenic Drugs - Coschignano, Maria Antonietta; De Ciuceis, Carolina; Agabiti-Rosei, Claudia; Brami, Valeria; Rossini, Claudia; Chiarini, Giulia; Malerba, Paolo; Famà, Francesca; Cosentini, Deborah; Muiesan, Maria Lorenza; Salvetti, Massimo; Petelca, Alina; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objective: Antiangiogenic therapies (tyrosine kinase inhibitors-TKI and direct anti-VEGF monoclonal antibodies) are being increasingly used in the treatment of solid tumors; hypertension represents a common side effect of these agents. Several mechanisms are involved in the development of hypertension, including microvascular rarefaction and other microvascular alterations. Therefore, the aim of our study was to evaluate whether TKI and direct anti-VEGF agents may affect the structure of retinal arterioles or capillary density. Design and Methods: We investigated 20 patients with a diagnosis of cancer who underwent a treatment with either a TKI or an anti-VEGF antibody. Patients were submitted to ambulatory monitoring blood pressure for blood pressure evaluation. Basal and total capillary density were assessed by capillaroscopy whereas, retinal arteriole morphology was measured by Adaptive Optics. Patients were evaluated before starting the antiangiogenic therapy (T0) and re-evaluated after 3 (T3) and 6 (T6) months after treatment. Fourteen patients completed the study. Results: Systolic and diastolic blood pressure values were similar in all patients at T3 and T6 compared to T0. However, during the study antihypertensive treatment was optimized (increased dose and/or addition of drugs) in 57% of patients (n = 8). No differences were observed in retinal arteriole structural parameters and in large artery stiffness. Basal capillary density was reduced by antiangiogenic drugs after 3 or 6 months. Conclusions: Our data suggest that an increase of antihypertensive treatment is necessary in patients treated with a TKI or a direct VEGF inhibitor, confirming pro-hypertensive effects of these drugs. However, under adequate blood pressure control, microvascular structure seem to be partially preserved, since a worsening of basal capillary density but no changes in retinal arteriole morphology were observed.